1995
DOI: 10.1149/1.2048696
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Species of Transition Metal Ions on Silicon Wafer in SC‐1 Solution

Abstract: Adsorption of transition metal ions such as Fe(III), Ni(II), and Zn(II) on silicon wafers in ammoniac hydrogen peroxide solution (SC-1 solution) has been studied. It was found by comparing the experimental results with the equilibrium calculations that the main adsorption species is the dissolved neutral hydroxide complex. This was supported by the calculated free energy change of adsorption of hydroxide complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 2 publications
1
50
0
Order By: Relevance
“…It has been reported that hydrolyzed iron species are formed in alkaline solutions and are highly active in the decomposition of hydrogen peroxide. At the pH of APM solution ($10.6 at 25°C), hydrolyzed iron species begin to form at the critical iron concentration of 5 Â 10 À8 mol L À1 (0.5 ppb) [22]. In previous studies aimed at determining the effect of iron concentration on hydrogen peroxide decomposition, iron was added in the Fe 3+ form to APM solutions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hydrolyzed iron species are formed in alkaline solutions and are highly active in the decomposition of hydrogen peroxide. At the pH of APM solution ($10.6 at 25°C), hydrolyzed iron species begin to form at the critical iron concentration of 5 Â 10 À8 mol L À1 (0.5 ppb) [22]. In previous studies aimed at determining the effect of iron concentration on hydrogen peroxide decomposition, iron was added in the Fe 3+ form to APM solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that all the particles are cubic, with a side length of 120 nm, it is found that the surface metal concentration before precipitation would be 3.2•10 Ϫ8 mol cm Ϫ2 or 2•10 16 atom cm Ϫ2 . This is 1000 times more than the saturation point found by Mori et al 10 This fact indicates that, if there is a saturation point in the case of etching of Si in KOH, it is at least 1000 times higher than in the case of SC-1. The low contamination level of the silicon oxide due to saturation makes it difficult to characterize the contamination using SEM.…”
Section: Discussionmentioning
confidence: 58%
“…These results were found for pH 11 and at a temperature of 80°C. Mori et al 10 have also performed calculations that compare the free energy change of adsorption for Fe(OH) x (x ϭ 0 to 4͒ as a function of pH ͑0-14͒. 10 has been reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal ions adsorb on the surface silicon dioxide layer. Since the metal adsorption is controlled by a natural equilibrium, 4 the IAP wafers that are prepared in a single solution have high wafer-to-wafer uniformity.…”
Section: Introductionmentioning
confidence: 99%